Wastewater reuse for alfalfa production in the Gaza Strip - Shomar, Basem; El-Madhoun, Fayeq; Yahya, Alfred (Water, air & soil pollution, 2010)
Geography, population growth, and politics combine to make the Gaza Strip a worst-case scenario for water resource planners. Potable water sources are shrinking while at the same time, the proportion of potable water used for irrigation is increasing. To assess whether water from wastewater treatment plants could be safely used for irrigation, this study collected 51 treated wastewater, 51 sludge, 44 soil, 30 alfalfa, and 24 oranges and lemon samples and analyzed the samples for major and trace elements. Both Inductively Coupled Plasma - Optical Emission Spectroscopy (ICP/OES) and X-ray fluorescence (XRF) were used for the determination of Ag, Al, As, B, Ba, Br, Ca, Cd, Co, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Ni, P, Pb, Rb, Se, Sr, Zn, Zr, Th, and U in digested and solid samples, respectively. Treated wastewater characteristics showed a very good agreement with the guidelines of many developed countries. Moreover, none of the tested parameters in soil showed concentrations exceeding their corresponding background values. For alfalfa, both ICP/OES and XRF showed Zn concentrations in leaves (36-42 mg/kg, respectively) higher than in root (19-31 mg/kg, respectively). The Cu showed also the same trend as Zn. No significant variation was observed between the concentrations of Cr and Mn in plant parts; concentrations of Co and Pb were two times higher in roots than in leaves and stems. The findings confirm that treated wastewater is safe to use for irrigation in Gaza. Collecting and reclaiming this water can contribute to wise use of each drop of water available.
Gesehen am 18.07.2023